High-Resolution Orthomosaics and Digital Elevation Models of Biogenic Structures in the German Wadden Sea - Tom K Hoffmann; Kai Pfennings; Jan Hitzegrad; Maike Paul; Achim Wehrmann; Nils Goseberg; Torsten Schlurmann (PANGAEA, 2025)
This dataset contains high-resolution (5 cm/pixel) orthomosaics and digital elevation models (DEMs) from unoccupied aerial vehicle (UAV) surveys of biogenic structures in the German Wadden Sea. Two Pacific oyster reefs (Kaiserbalje, Nordland) and one blue mussel bed (Nordstrand) were monitored between 2020 and 2022. The data, processed via structure from motion (SfM) and georeferenced, are provided as raster files (*.tiff), ready for GIS analysis. The Random Forest (RF) classification shapefiles support the mapping of biogenic structures. This dataset facilitates research on biogenic structure growth, sediment dynamics, and geomorphological processes in intertidal environments